Changing people demands to policies: The roles of elected representatives at Kubang Pasu District, Malaysia - Brahim, Malike; Mohamad, Musliza; Ahmad, Mohamad Zaki (Universiti Utara Malaysia, 2018)
People have various demands to the government. In the plural society in Malaysia, the demands are different for different groups striving to obtain access to finance, better healthcare, housing, subsidies, security and other human necessities. These and other demands are channeled to the government through elected representatives. However, not all demands will be fulfilled, they need to be evaluated and prioritized by the government before changes in public policies are made. Interviews were conducted with the elected representatives to scrutinize the problems faced by people in their constituencies. Also, questionnaires have been distributed to examine problems and issues at the grass root. The research findings indicate that people’s demands are divided into eight priorities such as education, housing, agriculture, animal husbandry, safety, facilities, religious issues and household issues. Basing on the political system theory, the demands are processed as input by the government and output is produced in the form of aids, projects, programs and plans arranged by the federal and various other agencies. Once policies are implemented, people give their feedback as the outcome from the policies’ implementation.